Bridging Markets, Building Alliances: Assessing the India-Australia Economic Cooperation through the Lens of Trade Liberalization and Geoeconomic Strategy - Aman, Arfia; Alam, Imran; Singh, Gopal Ji; Ghali, Zohra; Fatma, Ramla; Khan, Kareena (International Journal of Economics and Financial Issues, 2025)
India and Australia forged stronger connections, notably in the economic domain, during the period after their independence. The Free Trade Agreement, formally referred to as the Economic Cooperation and Trade Agreement, between India and Australia became operational in December 2022. This article aims to analyses India’s trading prospects with Australia. In order to accomplish the goal, a Revealed Comparative Advantage, Trade Intensity Index, and Trade Potential Index have been computed utilizing secondary data obtained from the UNCOMTRADE Database. The findings indicated that both nations had a notable edge in distinct goods. It signifies that there are some goods in which the nation is not engaging in competition with each other. This study examines the potential sectors for commodities where bilateral commerce might be advantageous, making a Free commerce Agreement (FTA) a mutually beneficial arrangement for both countries.